2013
DOI: 10.1152/ajpheart.00903.2012
|View full text |Cite
|
Sign up to set email alerts
|

AICAR administration ameliorates hypertension and angiogenic imbalance in a model of preeclampsia in the rat

Abstract: Banek CT, Bauer AJ, Needham KM, Dreyer HC, Gilbert JS. AICAR administration ameliorates hypertension and angiogenic imbalance in a model of preeclampsia in the rat. Am J Physiol Heart Circ Physiol 304: H1159 -H1165, 2013. First published February 15, 2013 doi:10.1152/ajpheart.00903.2012.-Previous studies suggest restoration of angiogenic balance can lower blood pressure and improve vascular endothelium function in models of preeclampsia. Our laboratory has recently reported exercise training mitigates hyperte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 39 publications
0
31
1
Order By: Relevance
“…Although various in vitro and in vivo models have been used to study the etiology of PE [38][39][40], such as exposure of trophoblast cells to hypoxia and hypoxia/reoxygenation [41][42][43][44], induction of 'PE-like' trophoblast cell metabolic alterations had not previously been demonstrated. Our data show that persistent exposure to 1% oxygen for 24 h was required to activate AMPK in HTR8/SVneo cells, indicating that trophoblast cells were resistant to low oxygenation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although various in vitro and in vivo models have been used to study the etiology of PE [38][39][40], such as exposure of trophoblast cells to hypoxia and hypoxia/reoxygenation [41][42][43][44], induction of 'PE-like' trophoblast cell metabolic alterations had not previously been demonstrated. Our data show that persistent exposure to 1% oxygen for 24 h was required to activate AMPK in HTR8/SVneo cells, indicating that trophoblast cells were resistant to low oxygenation.…”
Section: Discussionmentioning
confidence: 99%
“…Although Banek and colleagues have shown that pharmacological activation of AMPK in the Reduced Uterine Perfusion Pressure (RUPP)-induced PE rat model ameliorates hypertension [38], the protective effects of AMPK activation on PE are probably largely derived from its regulatory function on angiogenesis rather than on trophoblast invasion. Therefore, the timing and type of AMPK modulation should be carefully tailored to the intended effect.…”
Section: Discussionmentioning
confidence: 99%
“…These ELISAs will be referred to as either the rat VEGF ELISA or mouse VEGF ELISA for the remainder of the paper. Previous investigators have interpreted these ELISAs as measuring free (5,7,14) or total (20) VEGF; however, R&D Systems does not specify what the kits measure. Therefore, we have simply referred to these measurements as VEGF in the results and discussion.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, Lankhorst and coworkers 3 indicated that activation of the ET-1 axis may support the use of ET receptor antagonists for the treatment of angiogenesis inhibition-induced hypertension, especially because ET receptor stimulation in vascular smooth muscle cells results in VEGF production and mitogenesis in a mitogen-activated protein kinase pathway-dependent manner. What's more, Banek and colleagues 4 showed that AMP-activated protein kinase (AMPK) is stimulated during exercise and has been shown to increase expression of VEGF. Therefore, using a potent AMPK stimulator would increase circulating VEGF, improve angiogenic potential, decrease oxidative stress, and abrogate placental ischemiainduced hypertension.…”
Section: Vascular Endothelial Growth Factor: a Novel Potential Therapmentioning
confidence: 99%
“…Lastly, some hypothesize that TKIs can cause tumor cell apoptosis, leading to release of stored catecholamines and metanephrines and worsening hypertension. 4 Interestingly, in vitro studies in PC-12 rat pheochromocytoma cells suggest that sunitinib inhibits tyrosine hydroxylase activity thereby ultimately decreasing catecholamine production. 6 Based on the literature and our experience, we suggest that patients with malignant PCC/PGL receiving any systemic therapy should be evaluated for pretreatment with a-blockers or calcium channel blockers, similar to the perioperative blockade, to prevent exacerbation of hypertension.…”
mentioning
confidence: 99%